Pelaksanaan program Inpres desa tertinggal dalam perspektif pembangunan pedesaan - Priyadi, Unggul (Economic Journal of Emerging Markets, 2016)
In 1993 Indonesian overnment launched first IDT (Inpres Desa Tertinggal) program. IDT program is more than government effort to eliminate poverty, but a rural development strategy. It is directed to hike economic autonomy and to accelerate growth by increasing social economic activity based on decentralization principles.